PENERAPAN NOODWEER (PEMBELAAN TERPAKSA) DALAM PUTUSAN HAKIM/PUTUSAN PENGADILAN - Rani Angela Gea; Muhammad Hamdan; Madiasa Ablisar; Suhaidi Suhaidi (USU LAW JOURNAL, 2016)
ABSTRACT   The reasons for the negation of criminal (Straf Uitsluitings Gronden) are reasons that allow a person who has committed a criminal offense which meets formula, but can not be convicted. The defense forced (noodweer) is the reason for eliminating the illegitimacy (wederrechtelijkheid or onrechtmatigheid), then the reason for eliminating the nature of the crime (strafuitsluitings - grond) is also said to be a reason to justify or justify acts that generally constitute a criminal offense (rechtvaardigings - grond) called fait justificatief. The results showed that the Application of noodweer the verdict or the court's ruling, it must meet two main points, namely: There was an attack. Not against all attacks can be held defense, but in attack that meets the following requirements: instantaneous; which directly threatened; against the law; deliberately aimed at the body, politeness and possessions. There should be a defense against the attack. Defense actions must meet the following requirements: the defense should be and needs to be held; defense must involve the interests referred to in the legislation that is an attack on the body (lijf), politeness (eerbaarheid) and property (goed) belongs to himself or others . Keywords: Noodweer, Defence Emergency, The verdict of the Supreme Court of the Republic Indonesia